Characterization of Setophoma henanensis sp. Nov., causing root rot on peanut - Min Li; Di Liu; Mengke Wang; Kaidi Cui; Liting Chen; Leiming He; Lin Zhou (BMC Microbiology)
Abstract Background Peanut root rot is a common disease worldwide, which can cause serious economic losses to the peanut industry. In 2021, symptoms of peanut root rot were observed in five cities of Henan province, China, i.e., Xinxiang, Puyang, Pingdingshan, Zhumadian, and Nanyang. Results A total of 22 isolates of Setophoma sp. were obtained from 120 diseased peanut root samples. Based on the morphological characteristics and multilocus phylogenetic analyses with the sequences of ITS, LSU, TUB2, TEF-1a, and RPB2, these fungal isolates were identified as a new species of Setophoma spp., and named as Setophoma henanensis. Through Koch’s postulates, we demonstrated that S. henanensis could cause root rot disease in peanuts. Pathogenicity test revealed that S. henanensis could cause root rot symptoms in four different hosts, including corn, wheat, pepper, and Welsh onion, indicating that this species may have a wide host range. Furthermore, S. henanensis was sensitive to all tested fungicides, including difenoconazole, tetramycin, pyraclostrobin, and carboxin. Conclusions This is the first report of S. henanensis as a new pathogen of peanut root rot in the world. Furthermore, our findings will also provide a basis for further epidemiological research and the development of control strategies.